Serial study of phagocytic function in rat bovine serum albumin (BSA) nephritis. - Kawasaki, K. (1988)
We have examined the in-vitro role of polymorphonuclear leucocytes (PMNs) and macrophages in the degradation of immune complexes (ICs) at various points during the induction of rat bovine serum albumin (BSA) nephritis. Two types of experiments have been used. In one set (experiment A) preformed 125I-BSA-anti-BSA complexes (which consisted of heterologous (rabbit) antibodies) were incubated with peritoneal macrophages and PMNs from normal and nephritic rats at 37 degrees C for between 1 h and 24 h and the degradation rates of ICs were studied. In the other set (experiment B), homologous ICs prepared from antibodies derived from the sera of nephritic rats were examined using macrophages and PMNs from normal rats. In experiment A, the degradation of heterologous ICs by macrophages was decreased but degradation by PMNs was not decreased if the assays were performed 8 or 9 weeks after injection. Degradation by both macrophages and by PMNs was increased at weeks 10 and 11. In experiment B, the degradation of homologous ICs from the nephritic rats was increased markedly at week 9 and a relationship was observed between both the degradation and antibody titre and the value of the antigen binding capacity of 33% (ABC-33) during the course of nephritis. There was no difference between PMNs and macrophages in their ability to degrade homologous ICs from the nephritic rats.(ABSTRACT TRUNCATED AT 250 WORDS)